ACCIOLOGICAL CONCEPT OF A NEW EDUCATIONAL STRATEGY FOR TRAINING OF TEACHERS - Ivaniuk, Hanna (Educological discourse, 2018)
We consider the education of the 21st century as a process of preparing a young generation for life and work and as a means of productive changes in the state and the world dimension as a whole. The development of the education system in Ukraine is characterized by internal public inquiries and external factors that are actualized in the context of European integration. At the time – training of an innovative specialist, ready for intercultural communication and conscious protection of human virtues: individual freedoms and respect for it, culture of peace, etc. According to the results of the analysis of philosophical, historical and pedagogical sources, the status of pedagogical practice, the axiological concept of a new educational strategy of teacher training in a higher education institution is generalized and substantiated. Education is seen as a factor in harmonization in systems: man – man, man – nature, man – technology. The article gives a summary of the results of the study of the status of the identified problem in the practice of training the teachers of the first educational level (Bachelor) specialties «Preschool education», «Primary education». The revealed tendencies are characterized: divergence, which leads to the destruction of ties that could ensure the formation of a system of knowledge about man, nature, technology (technology) and society. Education directed towards the future should deviate from the rudiment of the knowledge-normative strategy of the Soviet model and build on values based on philosophical, ethical, aesthetic concepts. According to the results of the analysis of the study, the opinions of students, pedagogues-practitioners regarding the correspondence of the content of professional disciplines (pedagogy, psychology) to the needs of the individual, community and society are determined. A set of methods (poll, interviewing, questionnaires, pedagogical essay, mathematical statistics) allowed to reveal the dominance of moral values in the educational process (professional activity).